La industria automotriz en México durante las recientes crisis: reorganización productiva y perspectiva geopolítica - Arciniega, Rosa Silvia (Pontificia Universidad Católica del Perú, 2024)
The 2020-2021 global health crisis, the microcomponent shortage emergency from 2021 to current days and the multiple ongoing geopolitical tensions (especially between United States and China) continue to have an impact on the automotive industry. These events have generated disruptions in supply chains, which have highlighted the vulnerabilities of a production system that works Just in Time. In this context, nearshoring has gained significance as a strategy to ensure a resilient and efficient supply chain in terms of times and costs. The objective of this research is to describe the scenario of the automotive industry in Mexico during the recent crisis that have occurred since 2020, and that continue to impact the international trade context identifying nearshoring as a business strategy linked to a productive restructuring, with the aim of managing risks in a complex production network. It is concluded that the post pandemic context demands a reconsideration of the structure and organization of the productive activities of the Mexican automotive industry, with an impact not just at the sectoral level but also at the regional level. Furthermore, the increase in production costs in China also positions Mexico as an attractive trading partner, proposing to launch operations with similar products to the Asian manufacturers. The productive and geographic restructuring, which includes offshoring to reshoring with re-localization of companies and divisions, impose to consider the role that Mexico will play in the changing geopolitical and economic landscape.

La crisis sanitaria de 2020-2021, la escasez de microcomponentes desde 2021 hasta la fecha, y las múltiples tensiones geopolíticas en curso (especialmente entre Estados Unidos y China) han tenido un impacto significativo y continuo en la industria automotriz. Estos eventos han generado disrupciones en las cadenas de suministros, evidenciando las vulnerabilidades de una industria que trabaja bajo el sistema de producción Justo a Tiempo. En este contexto, el nearshoring ha adquirido relevancia como estrategia para asegurar una cadena de suministro resiliente y eficiente en lo que respecta a los parámetros temporales y económicos. El objetivo de esta investigación es describir el panorama de la industria automotriz en México durante las recientes crisis –iniciadas en el año 2020 y que aún persisten impactando el contexto del comercio internacional, identificando el nearshoring como una estrategia de negocios vinculada a una reestructuración productiva con el propósito de gestionar los riesgos en la compleja cadena de producción. Se plantea que el contexto postpandémico insta a una reconsideración de la estructura de las actividades productivas de la industria automotriz mexicana, la cual tiene un impacto no solo a nivel sectorial, sino también regional. Además, el aumento de costos de producción en China también posiciona a México como un socio comercial atractivo que posee la posibilidad de iniciar operaciones relacionadas con productos similares a los provenientes de Asia. Las reestructuraciones productivas y geográficas, que incluyen procesos de deslocalización y el retorno significativo de la producción a los países de origen (relocalización de empresas y divisiones), imponen la necesidad de considerar el rol que desempeñará México en el cambiante contexto geopolítico y económico.
The Mexican Automotive Industry Through the Recent Crisis: Productive Reorganization and Geopolitical Perspective
Keywords: Automotive industry; Global production network; Crisis; Strategies; Nearshoring; Industria automotriz; Red global de producción; Crisis; Estrategias; Nearshoring; https://purl.org/pe-repo/ocde/ford#5.07.00